2022
DOI: 10.1371/journal.pone.0279177
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefits for lower socioeconomic groups by improving bowel screening participation in South Australia: A modelling study

Abstract: Introduction The gap in bowel cancer screening participation rates between the lowest socioeconomic position (SEP) groups and the highest in Australia is widening. This study estimates the long-term health impacts and healthcare costs at current colorectal cancer (CRC) screening participation rates by SEP in South Australia (SA). Methods A Markov microsimulation model for each socioeconomic quintile in SA estimated health outcomes over the lifetime of a population aged 50–74 years (total n = 513,000). The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with previous studies that reported lower bowel screening uptake among more disadvantaged or remote areas in Australia [6,14,31] and globally. [8,12,32] That these patterns were evident across three non-overlapping consecutive time-periods indicates the stability of these associations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with previous studies that reported lower bowel screening uptake among more disadvantaged or remote areas in Australia [6,14,31] and globally. [8,12,32] That these patterns were evident across three non-overlapping consecutive time-periods indicates the stability of these associations.…”
Section: Discussionsupporting
confidence: 93%
“…Commonly cited reasons for the generally lower screening participation among people from more disadvantaged areas include differences in knowledge and attitudes, reduced responsiveness to disease prevention and health promotion messages and a lower engagement in healthy behaviors in general [ 8 , 14 , 31 , 33 ]. However, our results found that NBCSP participation rate in some areas categorized as most disadvantaged is higher than the national average, demonstrating that area-level disadvantage lacks sufficient specificity for identifying areas with poorer participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation